1999
DOI: 10.1007/s003359901182
|View full text |Cite
|
Sign up to set email alerts
|

A novel pleckstrin homology-related gene family defined by Ipl/Tssc3, TDAG51, and Tih1: tissue-specific expression, chromosomal location, and parental imprinting

Abstract: We previously described a gene, Ipl (Tssc3), that is expressed selectively from the maternal allele in placenta, yolk sac, and fetal liver and that maps within the imprinted domain of mouse distal Chromosome (Chr) 7/human Chr 11p15.5 (Hum Mol Genet 6, 2021, 1997). Ipl is similar to TDAG51, a gene that is involved in FAS/CD95 expression. Here we describe another gene, Tih1 (TDAG/Ipl homologue 1), with equivalent sequence similarity to Ipl. Structural prediction indicates that the products of these three genes s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0
10

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(98 citation statements)
references
References 27 publications
2
85
0
10
Order By: Relevance
“…However, although considered proapoptotic, TDAG51 is also up-regulated by IGF-I (48) and platelet-derived growth factor (51) through the activation of the Akt pathway (51), which is strongly involved in survival. TDAG51 regulation by IR-A may reflect a mechanism common to different growth factors and may underscore the fact that apoptosis is also regulated by the IR-A isoform, by both proapoptotic and antiapoptotic factors, as shown previously for IGF-IR (44,52,53).…”
Section: Differential Transcriptional Effects Of Insulin and Igf-ii 4supporting
confidence: 54%
“…However, although considered proapoptotic, TDAG51 is also up-regulated by IGF-I (48) and platelet-derived growth factor (51) through the activation of the Akt pathway (51), which is strongly involved in survival. TDAG51 regulation by IR-A may reflect a mechanism common to different growth factors and may underscore the fact that apoptosis is also regulated by the IR-A isoform, by both proapoptotic and antiapoptotic factors, as shown previously for IGF-IR (44,52,53).…”
Section: Differential Transcriptional Effects Of Insulin and Igf-ii 4supporting
confidence: 54%
“…TDAG51 is a member of a novel pleckstrin homology-related 2 J. Zhou and R. C. Austin, manuscript in preparation gene family that consists of Ipl/Tssc and Tih (20). Sequence analysis has revealed that TDAG51 contains a central motif resembling a pleckstrin homology domain and several distinctive C-terminal proline-glutamine and proline-histidine repeats, suggesting a role in transcriptional regulation and/or PCD (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…This view, however, has been challenged by the observation that T-cells from TDAG51 À/À mice do not display discernible defects in CD3/ TCR-dependent upregulation of CD95 expression or AICD. 13 Since there are several pleckstrin-homology domain-containing proteins with significant homology to TDAG51, [18][19][20][21] it might be possible that one of these homologues fulfills the role ascribed to TDAG51 in normal murine and human T-cells. In line with a dispensable role of TDAG51 in the regulation of AICD, we did not observe a correlation between TDAG51 expression and the induction of AICD in a set of AICDsusceptible and AICD-resistant human T-cell clones.…”
Section: Discussionmentioning
confidence: 99%